Metabolic Syndrome and Its Components Are Associated With Altered Amino Acid Profile in Chinese Han Population - Sun, Shuiya; He, Dongjuan; Luo, Cheng; Lin, Xihua; Wu, Jiahua; Yin, Xueyao; Jia, Chengfang; Pan, Qianqian; Dong, Xuehong; Zheng, Fenping; Li, Hong; Zhou, Jiaqiang (Frontiers in Endocrinology, 2022)
Abstract Objective: This study aimed to examine the association between amino acid metabolism and metabolic syndrome (MetS) and its components in Chinese Han population. Methods: This observational study enrolled 473 participants. Plasma concentrations of 28 amino acids were determined using high-performance liquid chromatography-tandem mass spectrometry (LC/MS) with an isotope internal standard method. Participants were divided into MetS (n = 72) and non-MetS (No MetS) groups (n = 401) to analyze the association between amino acids and MetS and its components. Results: MetS had a prevalence of 15.2% according to criteria.Plasma concentrations of isoleucine (Ile), leucine (Leu), valine (Val), tyrosine (Tyr), tryptophan (Trp), phenylalanine (Phe), glutamic acid (Glu), aspartic acid (Asp), alanine (Ala), histidine (His), methionine (Met), asparagine (Asn) and proline (Pro) were significantly higher in MetS group than in No MetS group (P < 0.05)，while Taurine (Tau) was significantly lower (P < 0.05). As MetS components were increased, the concentrations of these 13 amino acids increased significantly (P < 0.05), the concentration of Tau was decreased significantly (P < 0.05). Principal component analysis(PCA) was used, and 3 factors were extracted from the 14 amino acids. Factor1 and factor2 were significantly associated with MetS (odds ratio, 95% confidence interval; 1.723, 1.325-2.085, and 1.325, 1.043-1.684, respectively). 260 participants with no MetS were followed up effectively, and 42 participants developed to new-onset MetS within 5 years. We found the amino acid pattern of factor1 and Tau was related to the occurrence of future MetS. Early decrease of Tau could be predicted the occurrence of MetS. Conclusion: Participants with MetS exhibits an abnormal amino acid profile, and its components gradually increase when these amino acids are altered. Amino acid PCA profile can be employed for assessing and monitoring MetS risk. Finally, decreased Tau may be linked to the future development of MetS.